If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -36) = (2x + 26) Reorder the terms: (-36 + 3x) = (2x + 26) Remove parenthesis around (-36 + 3x) -36 + 3x = (2x + 26) Reorder the terms: -36 + 3x = (26 + 2x) Remove parenthesis around (26 + 2x) -36 + 3x = 26 + 2x Solving -36 + 3x = 26 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -36 + 3x + -2x = 26 + 2x + -2x Combine like terms: 3x + -2x = 1x -36 + 1x = 26 + 2x + -2x Combine like terms: 2x + -2x = 0 -36 + 1x = 26 + 0 -36 + 1x = 26 Add '36' to each side of the equation. -36 + 36 + 1x = 26 + 36 Combine like terms: -36 + 36 = 0 0 + 1x = 26 + 36 1x = 26 + 36 Combine like terms: 26 + 36 = 62 1x = 62 Divide each side by '1'. x = 62 Simplifying x = 62
| 8(2x-1)=2(8x+6) | | 4y=-8x+10 | | 49-3x=9-7x | | 5(x-7)=-2x+7 | | (3x-10)(8x-30)=180 | | 9w+4=5(w-8) | | (2x+3y)=3x | | 10+6h=34 | | 11x-10=(5x)-(9) | | 11/3=x-4/6 | | 7tanx+3=10tanx | | 1b+94a=94a | | 11x-10=5x-9 | | 5(5+7)=6(X+6) | | 24=(x*7)-(x*3) | | 10x+10y=2 | | 0.2x-2.9=2.9x+2.8 | | 1b+94a=24 | | e^1-5x=37 | | 2(x+6)-7= | | 8(7-1)=-24 | | 21=6g-9 | | 180=x(x-4)(x+9) | | (3c^2d^4)(-2c^2)= | | 0.25-2r=4 | | X(x-4)=4(x-5) | | 2x+46-3x= | | 2g+8=16 | | y+6=-9(x+10) | | 4x(10)2x-2=3x+4 | | a(n)=7+(n-1)(4) | | a(n)=7 |